A review of prediction models of total carbon emission for civil buildings in China - Yin, Wenlong; Zhang, Wenjie; Gong, Tongdan; Li, Xiaoming; Liu, Kangyong (Frontiers in Energy Efficiency, 2023)
The carbon emissions from the building sector are one of the major sources of carbon emissions globally. In order to address global climate change, the Chinese government has proposed the 3060 dual carbon goals. In this context, the government urgently needs a predictive model for calculating and forecasting the energy consumption and carbon emissions in the construction industry to help formulate decarbonization strategies. The review and analysis of a predictive model for the current total carbon dioxide emissions in the Chinese construction sector can provide a basis for calculating and predicting carbon emissions, as well as for formulating corresponding emission reduction policies. This article analyzes the Carbon emission factor and the methods of obtaining building energy consumption data, which are crucial for predicting carbon emissions. Furthermore, it examines the predictive models for total CO2 emissions in the Chinese construction sector and summarizes their respective advantages and limitations. Finally, it highlights the shortcomings of existing research in terms of carbon emission factors, energy consumption data, and accounting scope, while suggesting future research directions.